2003
DOI: 10.1038/sj.embor.embor830
|View full text |Cite
|
Sign up to set email alerts
|

The AVIT protein family

Abstract: Homologues of a protein originally isolated from snake venom and frog skin secretions are present in many vertebrate species. They contain 80-90 amino acids, 10 of which are cysteines with identical spacing. Various names have been given to these proteins, such as mamba intestinal protein 1 (MIT1), Bv8 (Bombina variegata molecular mass ~8 kDa), prokineticins and endocrine-gland vascular endothelial growth factor (EG-VEGF). Their amino-terminal sequences are identical, and so we propose that the sequence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 28 publications
(93 reference statements)
0
66
0
1
Order By: Relevance
“…Colipases are necessary for lipid hydrolysis by pancreatic lipases and interact with lipid micelles (van Tilbeurgh et al, 1999). The colipase fold is found in a wide range of proteins other than colipases, including, for example, toxins from funnel web spider (Szeto et al, 2000), black mamba (Boisbouvier et al, 1998) and frog skin (Bv8) as well as in protease inhibitors (Kaser et al, 2003). The structure of the colipase fold is solved and it consists of short b-strands connected by loops and stabilized by disulfide bonds, resulting in finger-like structures, that may serve as interactive surfaces (van Tilbeurgh et al, 1999).…”
Section: Physical Properties and Structure Of Dkk Proteinsmentioning
confidence: 99%
“…Colipases are necessary for lipid hydrolysis by pancreatic lipases and interact with lipid micelles (van Tilbeurgh et al, 1999). The colipase fold is found in a wide range of proteins other than colipases, including, for example, toxins from funnel web spider (Szeto et al, 2000), black mamba (Boisbouvier et al, 1998) and frog skin (Bv8) as well as in protease inhibitors (Kaser et al, 2003). The structure of the colipase fold is solved and it consists of short b-strands connected by loops and stabilized by disulfide bonds, resulting in finger-like structures, that may serve as interactive surfaces (van Tilbeurgh et al, 1999).…”
Section: Physical Properties and Structure Of Dkk Proteinsmentioning
confidence: 99%
“…Recently, a novel family of secreted proteins comprising about 80 amino acids and possessing the N-terminal amino acid sequence AVITGAC has been characterized and named the AVIT protein family (Kaser et al 2003). Among these members, endocrine gland-derived-VEGF (EG-VEGF) and Bombina variegata 8 (Bv8) represent a novel class of angiogenic factors with expression profiles restricted to endocrine glands and a few other tissues, and with selective mitogenic, motogenic, and prosurvival activities for endocrine glandderived endothelial cells (LeCouter & Ferrara 2003.…”
Section: Introductionmentioning
confidence: 99%
“…prokineticins ͉ angiogenesis ͉ G protein-coupled receptor B v8 (1,2) and endocrine gland-derived VEGF (EG-VEGF) (3), secreted proteins also referred to as prokineticin-2 and -1, respectively (4,5), are structurally related to a larger class of peptides that are defined by a five disulphide-bridged motif called a colipase fold (6)(7)(8). We previously demonstrated that these ligands promote proliferation of endothelial cells derived from the adrenal cortex and stimulate angiogenic responses in the ovary (3) and testis (2).…”
mentioning
confidence: 99%